Kurdistan Regional Government : Economic and Social Impact Assessment of the Syrian Conflict and ISIS Insurgency - Kulaksiz, Sibel (World Bank, Washington, DC, 2015)
The Syrian civil war, which began in 2011 and the ISIS (Islamic State in Iraq and Syria) insurgency which accelerated in June 2014 led to this report. These events caused tens of thousands to flee and many chose the relative safety of the Kurdistan Region of Iraq (KRI). They came as refugees from Syria and as Iraqi internally displaced persons (IDPs). This happened during a fiscal crisis which led to a 90% drop in fiscal transfers from the central government in Baghdad starting in early 2014. This quick note summarizes a report with the same title on the impact and stabilization costs of the influx of refugees and IDPs. Impact refers to the immediate economic and fiscal effects on the KRI economy and budget. Stabilization cost refers to the additional spending needed to restore the welfare of KRI residents.